Genetic and functional variation across regional and local scales is associated with climate in a foundational prairie grass. Issue 2 (18th April 2020) - Hoffman, Ava M.; Bushey, Julie A.; Ocheltree, Troy W.; Smith, Melinda D.
Summary: Global change forecasts in ecosystems require knowledge of within‐species diversity, particularly of dominant species within communities. We assessed site‐level diversity and capacity for adaptation in Bouteloua gracilis, the dominant species in the Central US shortgrass steppe biome . We quantified genetic diversity from 17 sites across regional scales, north to south from New Mexico to South Dakota, and local scales in northern Colorado. We also quantified phenotype and plasticity within and among sites and determined the extent to which phenotypic diversity in B. gracilis was correlated with climate. Genome sequencing indicated pronounced population structure at the regional scale, and local differences indicated that gene flow and/or dispersal may also be limited. Within a common environment, we found evidence of genetic divergence in biomass‐related phenotypes, plasticity, and phenotypic variance, indicating functional divergence and different adaptive potential. Phenotypes were differentiated according to climate, chiefly median Palmer Hydrological Drought Index and other aridity metrics. Our results indicate conclusive differences in genetic variation, phenotype, and plasticity in this species and suggest a mechanism explaining variation in shortgrass steppe community responses to global change. This analysis of B. gracilis intraspecific diversity across spatial scales will improve conservation and management of the shortgrass steppe ecosystem in the future.